Multiple Logistic Regression Model, Relationship between Maternal Nutritional Status, Maternal Condition History, and Maternal Knowledge about 1000 HPK on the Incidence of Stunting in Toddlers in Pandan Lagan Village - Andy Amir; M. Ridwan; Arnild Augina Mekarisce; Aini Zulaikah (Lembaga Pengembangan Kinerja Dosen, 2022)
One of the stunting locations in East Tanjung Jabung Regency is located in Geragai Sub-district, Pandan Lagan Village. According to data from the Puskesmas in 2019, the incidence of stunting in Pandan Lagan Village was 35 toddlers, in 2020 it was 17 stunting children out of a total of 70 children in Pandan Lagan Village. The purpose of this study was to determine the relationship between maternal nutritional status, history of maternal conditions, and maternal knowledge about 1000 HPK with the incidence of stunting in Pandan Lagan Village. This type of research is quantitative research, using a cross-sectional approach. The number of samples to be studied with the Lemeshow Formula is 45 respondents. The dependent variable is stunting and the independent variables are maternal nutritional status (pre-pregnant maternal BMI and weight gain during pregnancy), history of maternal conditions (maternal age during pregnancy, birth spacing), and maternal knowledge about 1000 HPK. The research instrument used a questionnaire sheet, then the data was processed through data editing, data coding, data entry, data cleaning, and data processing, then analyzed univariate, bivariate with a chi-square test, and multivariate with multiple logistic regression test. Based on the results of the study, there is a relationship between pre-pregnancy maternal BMI with a risk of 4,464 times, weight gain with a risk of 3,75 times, maternal age during pregnancy with a risk of 3,0 times, and spacing of babies with a risk of 2,444 times with the incidence of stunting. There is no relationship between maternal knowledge about 1000 HPK and the incidence of stunting with a p-value = 0,114, and it is known that the pre-pregnancy mother's BMI variable is the variable that has the greatest influence on infants with stunting nutritional status (odds ratio = 15,943). For this reason, it is expected to be more intensive in educating couples of childbearing age, pre-pregnant mothers, or early on to adolescent girls to pay attention to factors that affect stunted children, especially to have an ideal BMI so that it will reduce the risk of having children with stunted nutritional status.